Description of Renal Biopsy in Frequently Relapsing and Corticosteroid Non Responsive Nephrotic Syndrome in Childhood - D. Bahrun; M. Nazir; K. Yangtjik N. (Indonesian Pediatric Society, 1988)
A study of 71 children with nephrotic syndrome admitted to the Department of Child Health, Medical School, Sriwijaya University Palembang General Hospital between November 1981 and November 1983 has been reported. Of the 71 children, there were 50 (70.4%) boys and 21 (29.6%) girls, in which 31 were less than 6 years of age. During the first eight weeks complete rem1sswn was found in 66 patients. The other five were steroid resistant. Among the 66 patients who responded to steroid, 61 had remission with the first 4 weeks. Further observation up to two years, 3 patients were still in remission, 36 had one relapse and 22 had frequent relapses. The other 5 patients, who had remission on the second 4 weeks, one had one relapse, two had frequent relapses and the other two were not available for follow up. Renal biopsy was performed in 31 patients. The representative results of the renal biopsy were found in only 20 patients : Eleven patients showed minimal change nephrotic syndrome (MCNS). Ten of these patients had frequent relapses while one patient was steroid resistant. Two had renal insufficiency. Three patients had focal glomerulosclerosis (FGS); two of them were frequently relapsing patients and the other one had steroid resistant. Four patients had mesangial proliferative glomerulonephritis (Mes. PGN). All of them had frequent relapses. One patient with diffuse proliferative glomerulonephritis (DPGN) was steroid resistant. One patient with crescentic glomerulonephritis (CrGN) was also steroid resistant.